Assessment of proximal tubular sodium reabsorption during water diuresis in patients with heart disease - Gibson, D. G. (1970)
In order to examine the relation between cardiac state and the capacity to excrete a water load, 10 normal subjects and 61 patients with heart disease were studied during water diuresis. Under these conditions, urine flow approximates to the rate of delivery of filtrate, and therefore of sodium, from the proximal tubule of the kidney to the loop of Henle, while free water clearance is a function of distal sodium reabsorption. In 12 patients with complete heart block, ventricular pacing was associated with increased urine flow and free water clearance. Oral propranolol in 3 normal subjects and in 9 patients with intact atrial septa caused a reduction, and oral practolol in 4 normal subjects and 8 patients caused no change. In 6 patients with atrial septal defect, propranolol was without effect. Maximum urine flow correlated with left ventricular end-diastolic pressure but not mean left atrial pressure in 16 patients with chronic rheumatic heart disease. In 7 patients with ischaemic heart disease, maximum urine flow was higher than in those with chronic rheumatic heart disease and similar increase in left ventricular end-diastolic pressure. These results reflect a close relation between proximal tubular sodium reabsorption and cardiac state, and suggest that inappropriate sodium reabsorption at this site may contribute to fluid retention in heart disease.